2021
DOI: 10.15252/embj.2020104509
|View full text |Cite
|
Sign up to set email alerts
|

PIF1 helicase promotes break‐induced replication in mammalian cells

Abstract: Break‐induced replication (BIR) is a specialized homologous‐recombination pathway for DNA double‐strand break (DSB) repair, which often induces genome instability. In this study, we establish EGFP‐based recombination reporters to systematically study BIR in mammalian cells and demonstrate an important role of human PIF1 helicase in promoting BIR. We show that at endonuclease cleavage sites, PIF1‐dependent BIR is used for homology‐initiated recombination requiring long track DNA synthesis, but not short track g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 82 publications
2
71
0
Order By: Relevance
“…demonstrated recently, the loss of the BIR factor PIF-1 can be exploited for selective killing of cells made to rely on this HR subpathway by the concurrent deletion of FANCM, revealing a new synthetic lethality relationship and an approach to target PIF-1 mutant cancer cells (Li et al, 2021). Also, it is known that the HR factor ATRX is defective in a variety of tumors that are commonly using the alternative lengthening of telomeres (ALT) mechanism of telomere maintenance (representing around 10-15% of all cancers; Dilley and Greenberg, 2015).…”
Section: Clinical Implications Of Hr Subpathway Choicementioning
confidence: 99%
“…demonstrated recently, the loss of the BIR factor PIF-1 can be exploited for selective killing of cells made to rely on this HR subpathway by the concurrent deletion of FANCM, revealing a new synthetic lethality relationship and an approach to target PIF-1 mutant cancer cells (Li et al, 2021). Also, it is known that the HR factor ATRX is defective in a variety of tumors that are commonly using the alternative lengthening of telomeres (ALT) mechanism of telomere maintenance (representing around 10-15% of all cancers; Dilley and Greenberg, 2015).…”
Section: Clinical Implications Of Hr Subpathway Choicementioning
confidence: 99%
“…In fact, unlike other DSBs, DSBs at collapsed forks are single ended, with no second end available for classical HR repair. These breaks can be processed by a replication-coupled repair named break-induced replication (BIR), a conservative DNA synthesis mechanism described as an HR-based repair pathway for one-ended DNA DSBs, which has been studied extensively in budding yeast [99] and more recently in mammalian cells [100]. BIR initiates at the broken forks, proceeds through the invasion by the broken chromosome of its homologous duplex, and moves as a D-loop along the length of the chromosome.…”
Section: The Critical Action Of Polθ In Tmejmentioning
confidence: 99%
“…Finally, recent work has shown that Pif1 is also necessary for BIR in human cell lines [ 138 ]. Importantly, this study demonstrated that the breast cancer-associated Pif1 mutant L319P, which resides within the Pif1 family signature motif, was defective for BIR [ 138 ].…”
Section: Srs2 and Pif1 As Model Systems For Understanding Sf1a And Sf1b Helicasesmentioning
confidence: 99%
“…Finally, recent work has shown that Pif1 is also necessary for BIR in human cell lines [ 138 ]. Importantly, this study demonstrated that the breast cancer-associated Pif1 mutant L319P, which resides within the Pif1 family signature motif, was defective for BIR [ 138 ]. This work provides crucial evidence suggesting that not only is the role of Pif1 in BIR is likely to be broadly conserved among eukaryotes, but also providing a direct indication that BIR (and Pif1) may play roles in human genome integrity and cancers.…”
Section: Srs2 and Pif1 As Model Systems For Understanding Sf1a And Sf1b Helicasesmentioning
confidence: 99%